Perlindungan Hukum Masyarakat Terhadap Hak Atas Tanah Ber-Status Quo Di Pulau Galang - Lia Nuraini; Dewi Haryanti (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The land problem in Galang Island started from the unclear division of authority between the Batam Regional Authority and the Batam City Government as well as the land status of the Galang Island area which led to the status quo. Meanwhile, the community already has their rights, but is considered to be in an illegal location. The formulation of the problem in this research are first, how is the arrangement of the authority of land management rights in Galang Island? Second, how is the legal protection of the people who hold land rights with status quo in Galang Island area? This is a normative legal research with historical and conceptual approaches. Retrieval of legal material through literature study and document study with qualitative analysis techniques. The results of the study concluded that land management rights were given to the Chairman of the Batam Concession Agency (BP) who was ex officio led by the Mayor of Batam. Other land problems arose from the Decree of the Minister of Forestry Number 307 / Kpts-II / 1986, namely that the Galang area was included as a forest area and the determination of the status quo that had an impact on the community. The safeguards undertaken by the National Land Agency (BPN) are by not issuing land title certificates in Galang and for the land rights owned by the community if the Batam Concession Agency wants to acquire land in Galang which already has the status of land rights must compensate for the plants or existing buildings on the land.